THE RELATIONSHIP BETWEEN ENTEREPRENEURSHIP INTEREST WITH THE LEARNING RESULT OF INDUSTRIAL WORK PRACTICE OF TWELVE STUDENTS (TKR) SMK KARSA MULYA PALANGKA RAYA ACADEMIC YEAR 2016/2017 - Muhammad Nazarudin (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2019)
Facing the ASEAN Economic Community (MEA) Vocational High School (SMK) has claimed to produce the output that has high competency and skill. By through industrial working practice, students were able to face competition increasingly rigorous work. To produce results industry work practices, students have to be encouraged by teacher and school to arouse an interest in entrepreneurship, desire, and willingness to be ready encounter work atmosphere. Based on the author's background, research aims to find out the relationship with learning outcomes entrepreneurship interest in industrial working practice of students at SMK Karsa Mulya Palangka Raya. The methods used in this study is quantitative research using research correlation approaches to find the relationship with learning outcomes entrepreneurship interest in industrial working practice. The population in this research is the whole of class XII TKR SMK Karsa Mulya Palangka Raya at academic year 2016/2017 conducted for total number of 57 students. The sample used in this study is students of class XII TKR A with 30 students with sampling techniques applied in this research. The total sample is all the populations. Entrepreneurship interest instruments before undertaking research has conducted the trials of instruments in SMKN 1 Palangka Raya with the number of respondents at around 21 students. Data collection techniques using questionnaire form and documentation in the form of the value of the results of the study industrial working practice of grade XII TKR. Test of normality is obtained that data with the Gaussian results of entrepreneurship learning interest in industrial working practice of students. The research results obtained by the author that is there is a significant relationship between interest in entrepreneurship learning outcomes of industrial working practice to students in class XII TKR SMK Karsa Mulya Palangka Raya on academic year 2016/2017. It is based on the results of the calculation of the coefficient correlation analysis which r value at 0.721 turned out to be located above the 5% significant level of 0.388. In addition it also can note that large contributions toward the learning outcomes entrepreneurship interest in industrial working practice of students in class XII TKR SMK Karsa Mulya Palangka Raya at academic year 2016/2017 at well about 52% while there is 48% determined by other factors.